(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
Language plays an important role in society, and each country has its own language units, and citizens speak these rules. The following linguistic units and technologies will be studied in the Department of Linguistics. This article is written on the differences between American and British English and is covered in full.